Characterisation and antioxidant activity of polysaccharide iron (III) complex in Qingzhuan Dark Tea - ZHOU,Hongfu (2022)
Abstract Anaemia, caused by iron deficiency, is a common disease in some parts of the world. A traditional medicine for treating anaemia resulting from iron deficiency is inorganic iron, which is represented by ferrous sulfate. However, serious irritation to the gastrointestinal tract is one of the side effects caused by inorganic iron. We extracted the tea polysaccharide (TPS) from Qingzhuan Dark Tea and employed a green technology to prepare a polysaccharide–iron [TPS-Fe(III)] complex. We further characterised the structure through thermogravimetric analysis, molecular weight analysis, atomic absorption spectroscopy, Fourier-transform infrared spectroscopy, ultraviolet spectroscopy (UV), 1H nuclear magnetic resonance spectroscopy, scanning electron microscopy, X-ray diffraction analysis, X-ray photoelectron spectroscopy, and atomic mechanics microscopy. We performed a comparative evaluation of the antioxidant properties of the TPS-Fe(III) complex and TPS. The results indicated that the antioxidant activity of the TPS-Fe(III) complex is superior to that of TPS. The scavenging activity was determined using 2,2-diphenyl-1-picrylhydrazyl, hydroxyl, superoxide anion, and 2,2'-azobis-(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activity assays and malondialdehyde inhibition assay. The structure of the TPS-Fe(III) complex formed by the complexation of the tea polysaccharide with iron ions was highly stable, which significantly improved its antioxidant activity in vitro. Thus, the TPS-Fe (III) complex can provide additional health benefits compared with other typical non-antioxidant iron nutritional supplements.